PsychNow! Interactive experiences in psychology - Jeffcoat, Kendra; Wadsworth/Thomson Learning (Firm) (Belmont: Wadsworth/Thomson Learning, 2004)
Provides the user with thirty-nine learning modules in eight areas of psychology. Includes research experiments, collaborative labs with chat and discussion groups, multimedia simulation, videos, and quizzes.
Απαιτήσεις συστήματος: PC with Pentium-II 233 MHz; 32MB RAM (64MB recommended); Windows 98 SE or later (except NT); 800x600, 16-bit High Color display; 16 bit sound card; speakers or headphones; 8x CD-ROM
Απαιτήσεις συστήματος για Mac: PowerPC Processor or later; 64MB RAM; MAC OS 8.6 or later; 800x600, 16 bit High Color display; speakers or headphones; 8x CD-ROM
Τίτλος από την ετικέτα του CD-ROM
Keywords: Psychology